Marker profile of myocardial remodeling in different etiopathogenetic forms of arterial hypertension in the experiment - Yu. M. Kolesnyk; M. I. Isachenko (Patologìâ)
The aim was to determine the morphodensitometric parameters of cardiomyocytes and features of the marker profile of remodeling in the left ventricular myocardium of rats with experimental hypertension of different etiopathogenetic forms.